Artificial worlds and artificial minds: Authenticity and language learning in digital lifeworlds - Blair Matthews (Journal of Responsible Technology, 2025)
Language learning is increasingly being extended into digital and online spaces that have been enhanced by simulated reality and augmented with data and artificial intelligence. While this may expand opportunities for language learning, some critics argue that digital spaces may represent a pastiche or a parody of reality. However, while there are genuine issues, such criticisms may often fall back on naïve or essentialist views of authenticity, in particular by narrowing language learning scenarios to real-life or genuine communication. I argue that research undersocialises authenticity by not taking social relations into sufficient consideration, which denies or elides the ways that authenticity is achieved. In this conceptual paper, I offer a relational account of authenticity, where I conceive digital environments within a stratified ontological framework, where authenticity is not inherent in individuals or texts, but instead emerges from complex social contexts. Authenticity, then, does not refer to authenticity of texts or “being oneself”, but authenticity in relation to others. A stratified ontology provides opportunities to extend relations with others, offering what is described as a “submersion into a temporary agency”, where language learners can experiment with the social order in order to achieve authenticity of themselves in the target language. Finally, I present a relational pedagogy based on responsiveness, where feedback is distributed among disparate human and technical actors which facilitate, problematise or endorse authenticity.